Caracterização agronômica do camapu (Physalis angulata L.), qualidade pós colheita e aproveitamento tecnológico dos frutos - Oliveira, Amélia Augusta de Lima Ajuricaba (Instituto Nacional de Pesquisas da Amazônia - INPA, 2018)
The camapu contain in their fruits, leaves, branches and roots essential nutrients and micronutrients such as minerals, fibers, vitamins and various secondary compounds of phenolic nature, these compounds depend on their chemical structure and concentration on food, these concentrations are largely influenced by factors genetic, environmental conditions, form of cultivation, degree of maturation, plant variety, among others. The objective of this work was to verify the influence of the different fertilizations during the development of P. angulata in relation to the physical-chemical properties, to develop products from the fruits and to evaluate conservation methods. The experimental design was a randomized block with six treatments and five replicates, with two sources of organic fertilization (chicken manure and bovine manure) and one chemical (NPK 60-80-26). Agronomic potential was evaluated using agronomic characters: plant height (cm), stem diameter (mm), total dry mass (%), accumulation of minerals in the leaves, fruit production, physical analysis of fruits in natura (g), biometrics (mm) (transversal and longitudinal diameter) and density, the fruits and products were characterized as moisture contents, lipids, pH, soluble solids content, ashes, proteins and carbohydrates, energetic value, based on the values of lipids, proteins and carbohydrates provide 9, 4 and 4 kcal. g-1, and the determination of water activity. The color was determined by calculating the angle Hue (h °) and the variance in storage time through the delta calculations. Fruit minerals were determined by atomic absorption spectrometry. The results showed that the fertilizations that presented the best responses for P. angulata cultivation were chemical fertilizations (NPK) and the interactions between chemical and organic fertilization (tanned bovine manure and NPK), for post-harvest quality, nutritional compounds and (NPK) and interactions between chemical and organic fertilization (tanned poultry manure and NPK) and (tanned bovine manure and NPK). The use of the modified atmosphere packaging promoted the effective preservation of the fruits in nature until the fourth month, the lyophilization presented the best responses for the physical-chemical characteristics and post-harvest conservation during the 150 days of storage and obtained a higher acceptability index.
Keywords: Camapu; Nutrientes; physalis Angulata L.; Adubações